The Nigerian statements of accounting standards and ribh (profit) in an islamic economy (2012)
As a measure of productivity and as an essential prerequisite for investment, profit is universal and fundamental to economic activities. A lot of research conducted over the years on Islamic finance and interest-based economic-system has been concerned basically with the macro-economic variable-interest (riba). However, the subject, profit (ribh), in relation to both conventional and Islamic accounting standards, has almost totally been neglected. This paper, therefore, investigates the determination of profit in line with the Nigerian Statements of Accounting Standards (SAS), conventional economics and Islamic economic perspectives. Relevant provisions stated in SAS 1 as regards the determination of profit are also applicable in an Islamic economic system. However, Islamic accounting uses both historical cost concept and current valuation inasmuch as the items considered are Shari‘ah-compliant. Risk alone, or risk and sacrifice, cannot make one entitled to profit. The paper makes a clear distinction between interest and profit and states why the former is not allowed in Islamic Banking. The cause of profit should be sales and services. Interest-based income and expenses that are recognised in SAS and conventional economics for profit determination are prohibited in Islamic accounting. Profit sharing ratio is mutually agreed upon between the financiers and the finance users in some Islamic financial products, while the buyer is not informed of the actual cost and the profit margins in other products.